The influence of dividend policy on the performance of mining companies: corporate governance as a moderating variable - Wau, Marselino (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2021)
The mining industry is an important industry for the central government as a source of funds to finance the country's development. Therefore, the performance of companies in this industry has been being an interest of academics and practitioners. However, less attention has been given to the role of corporate governance in moderating the relationship between dividend policy and performance. with the uniqueness of Indonesia's corporate governance system, this study will enrich the dividend policy and corporate governance literature. This study aims to investigate the corporate governance role in moderating the relationship between dividend policy and performance. Besides, this study also looks at the effect of dividend policy and performance. with a final sample of 21 companies for 3 years, we use the Moderated Regression Analysis (MRA) Before the regression run, we conduct several analyses, such as normality. The means score of each variable Return On Assets, Dividend Payout Ratio, Public Ownership, Company Age, and Company size hows that 4.77%, 32%, 29.6%, 23 years, and Rp. 13,6 T. Testing the first hypothesis in this study shows that the dividend payout ratio is accepted in a positive direction, the second hypothesis is Public Ownership, Company Age, Company Size, is rejected and the third hypothesis is Return On Assets is accepted at 10%. The interaction of dividend policy and corporate governance on performance is explained by agency theory. In practice, companies must implement corporate governance effectively.